Reasons for physician‐related variability in end‐of‐life decision‐making in intensive care. Issue 8 (21st May 2021) - Nordenskjöld Syrous, Alma; Malmgren, Johan; Odenstedt Hergès, Helena; Olausson, Sepideh; Kock‐Redfors, Maria; Ågård, Anders; Block, Linda
Abstract : Background: There is increasing evidence that the individual physician is the main factor influencing variability in end‐of‐life decision‐making in intensive care units. End‐of‐life decisions are complex and should be adapted to each patient. Physician‐related variability is problematic as it may result in unequal assessments that affect patient outcomes. The primary aim of this study was to investigate factors contributing to physician‐related variability in end‐of‐life decision‐making. Method: This is a qualitative substudy of a previously conducted study. In‐depth thematic analysis of semistructured interviews with 19 critical care specialists from five different Swedish intensive care units was performed. Interviews took place between 1 February 2017 and 31 May 2017. Results: Factors influencing physician‐related variability consisted of different assessment of patient preferences, as well as intensivists' personality and values. Personality was expressed mainly through pace and determination in the decision‐making process. Personal prejudices appeared in decisions, but few respondents had personally witnessed this. Avoidance of criticism and conflicts as well as individual strategies for emotional coping were other factors that influenced physician‐related variability. Many respondents feared criticism for making their assessments, and the challenging nature of end‐of‐life decision‐making lead to avoidance as well as emotional stress. Conclusion: Variability in end‐of‐life decision‐making is an important topic that needs further investigation. It is imperative that such variability be acknowledged and addressed in a more formal and transparent manner. The ethical issues faced by intensivists have recently been compounded by the devastating impact of the COVID‐19 pandemic, demonstrating in profound terms the importance of the topic.